SOCIO-RELIGIOUS HARMONY INDEX IN PERAK - ZULKEFLI, MOHD IKHWAN IZZAT (2021)
Socio-religious harmony is crucial to ensure national and political stability. Living in a multi-religious society is challenging to avoid the presence of inter-religious issues.